Lead Metal in Water and Sediment: A Case Study of Rumbia River - Deasy Natalia Botutihe; Sri Wanti Sappe; Ahmad Kadir Kilo; Jafar La Kilo; Akram La Kilo (The University of Mataram, 2021)
The purpose of this study was to determine and analyze the levels of leadcontained in the water and sediments of the Rumbia River. This research was conducted in a quantitative manner. Lead levels were measured using Atomic Absorption Spectrophotometer (SSA) of Simatzu AA 500. The results showed that the leadcontent in Rumbia River water for point A1 was undetectable whereas point 2 and 3 were 0.001 mg/kg. In sediments, at point A1 is 1.8 mg/kg and at points 2 and 3 were 0.9 mg/kg. The level of Pb in Rumbia River water is still below the water quality standard limit for marine biota determined by the Ministry of Environment No. 51 of 2004. Similarly, lead levels in sediments are below the threshold standard for sediment quality based on sediment quality guidelines for metals and associated levels of concern to be used in doing assessments of sediment quality. In general, it can be said that the concentration of lead in the Rumbia River is still at a harmless level. However, socio-economic conditions that continue to change over time can cause changes in the level of water pollution. So there needs to be an effort and public awareness in maintaining the occurrence of increased levels of pollutants in the Rumbia River.